Effect of the itinerant electron density on the magnetization and Curie temperature of Sr2FeMoO6 ceramics. Issue 51 (14th August 2018) - Wang, Jin-Feng; Shi, Teng-Fei; Zhuang, Zhao-Tong; Gao, Qian-Qian; Zhang, Yan-Ming
Abstract : T C of C6 exhibits a significant rise of 75 K over that of C2, resulting from introducing excess Mo in Sr(2− y ) Na y Fe(1− x ) Mo(1+ x ) O6 . Abstract : The itinerant electron density ( n ) near the Fermi level has a close correlation with the physical properties of Sr2 FeMoO6 . Two series of single-phase Sr(2− y ) Na y FeMoO6 ( y = 0.1, 0.2, 0.3) and Sr(2− y ) Na y Fe(1− x ) Mo(1+ x ) O6 ( y = 2 x ; y = 0.1, 0.2, 0.3) ceramics were specially designed and the itinerant electron density ( n ) of them can be artificially controlled to be: n = 1 − y and n = 1 − y + 3 x = 1 + 0.5 y, respectively. The corresponding crystal structure, magnetization and the ferromagnetic Curie temperature ( T C ) of two subjects were investigated systematically. The X-ray diffraction analysis indicates that Sr(2− y ) Na y FeMoO6 ( y = 0.1, 0.2, 0.3) have comparable Fe/Mo anti-site defect (ASD) content in spite of decreased n . However, a drastically improved Fe/Mo ASD can be observed in Sr(2− y ) Na y Fe(1− x ) Mo(1+ x ) O6 ( y = 2 x ; y = 0.1, 0.2, 0.3) caused by the intrinsic wrong occupation of normal Fe sites with excess Mo. Magnetization–magnetic field ( M – H ) behavior confirms that it is the Fe/Mo ASD not n that dominantly determines the magnetization properties. Interestingly, approximately when n ≤ 0.9, T C of Sr(2− y ) Na y FeMoO6 ( y = 0.1, 0.2, 0.3) exhibits an overall increase with decreasing n, which is contrary to the T C response in electron-doped SFMO. Such abnormal T C is supposed to relate with the ratio variation of n (Mo)/ n (Fe). Moreover, when n ≥ 1, T C of Sr(2− y ) Na y Fe(1− x ) Mo(1+ x ) O6 ( y = 2 x ; y = 0.3) exhibits a considerable rise of about 75 K over that of Sr(2− y ) Na y Fe(1− x ) Mo(1+ x ) O6 ( y = 2 x ; y = 0.1), resulting from improved n caused by introducing excess Mo into Sr(2− y ) Na y FeMoO6 . Maybe, our work can provide an effective strategy to artificially control n and ferromagnetic T C accordingly, and provoke further investigation on the FeMo-baseddouble perovskites.